2017
DOI: 10.18061/dsq.v37i2.5487
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Mental Disability by College and University Faculty: The Negotiation of Accommodations, Supports, and Barriers

Abstract: High-profile shootings and student suicides have made mental health issues on college campuses a major national issue. College students are usually the focus of this conversation, while little attention beyond anecdotal accounts has been paid to faculty with mental health issues. In response to this lack of broad-scale research, a first-of-its-kind cross-institutional survey of faculty with mental disabilities was conducted. Respondents self-identified as faculty with mental disabilities, mental illness or men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…These claims are communicated in interactions between disabled workers and their employers, potential employers, and colleagues, and the hegemonic power of normative workplace commonplaces often leaves disabled workers with the challenging rhetorical labor of destabilizing commonplaces to gain access. Whereas previous researchers identified access barriers like employer attitudes, biases, and lack of knowledge (Capella McDonnall et al, 2014;Foster & Wass, 2013;Kitchin et al, 1998;Lynch, 2013;Price et al, 2017;Sarrett, 2017), and sociologists identified everyday interactions in workplaces as sites where access is often negotiated (Engel & Munger, 2003;O'Brien, 2004), this study specifically identifies five normative workplace commonplaces that provide rhetorical resources for ableist claims about work and working bodies. This study answers calls in business communication for more theoretical knowledge of interpersonal communication (DeKay, 2012;Hynes, 2012;Robles, 2012) by demonstrating how ableist assumptions about work are often implicitly reinforced in interpersonal communication.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These claims are communicated in interactions between disabled workers and their employers, potential employers, and colleagues, and the hegemonic power of normative workplace commonplaces often leaves disabled workers with the challenging rhetorical labor of destabilizing commonplaces to gain access. Whereas previous researchers identified access barriers like employer attitudes, biases, and lack of knowledge (Capella McDonnall et al, 2014;Foster & Wass, 2013;Kitchin et al, 1998;Lynch, 2013;Price et al, 2017;Sarrett, 2017), and sociologists identified everyday interactions in workplaces as sites where access is often negotiated (Engel & Munger, 2003;O'Brien, 2004), this study specifically identifies five normative workplace commonplaces that provide rhetorical resources for ableist claims about work and working bodies. This study answers calls in business communication for more theoretical knowledge of interpersonal communication (DeKay, 2012;Hynes, 2012;Robles, 2012) by demonstrating how ableist assumptions about work are often implicitly reinforced in interpersonal communication.…”
Section: Discussionmentioning
confidence: 80%
“…8). While Price et al (2017) have resisted bureaucratic approaches to access, more research is needed on specific rhetorical strategies that employers can use for collective accountability.…”
Section: Implications For Researchmentioning
confidence: 99%
“…Some authors argue that mental health problems in academia are widespread and constitute an 'invisible crisis' (Price et al 2017;Bira et al 2019). This point of view may reflect anecdotal evidence of life experiences, but to our knowledge there is limited systematic empirical research concerning mental health issues in postdoctoral researchers, research and teaching fellows, or professors.…”
Section: Mental Disorders In Academiamentioning
confidence: 99%
“…For example, in their research with academic staff in the USA, Price and Kerschbaum () found that fear of disclosure was related to anxieties about losing credibility and respect, being the subject of gossip and being stigmatised as “weak” and “unprofessional.” Price et al. () show how these anxieties are compounded by typical institutional approaches to mental health. Institutional responses typically individualise responsibility for requesting support (also Mullings et al, ), position individual disclosures as “problems” to be solved (also Parizeau et al, ), and so often make individuals feel distressingly “visible,” other, awkward or out‐of‐line.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional responses typically individualise responsibility for requesting support (also Mullings et al, ), position individual disclosures as “problems” to be solved (also Parizeau et al, ), and so often make individuals feel distressingly “visible,” other, awkward or out‐of‐line. Little wonder, then, that many studies of (un)wellness in the neoliberal academy highlight experiences of considerable unease and unhappiness occasioned by “covering‐up” mental ill‐health in the workplace as individuals seek to “pass” as normatively‐able (England, ; Price et al., ) and adopt enclosive, non‐disclosive tactics in relation to their conditions and needs (Horton & Tucker, ).…”
Section: Introductionmentioning
confidence: 99%